Menunda kerusakan buah sawo (Manilkara zapota (L.) van Royen) dengan berbagai lama penyinaran UV-C dan penyimpanan pada suhu rendah - Sri Trisnowati, Suyadi, Patmi Sera Wahyuni, dan Nur Adhayati (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2012)
ABSTRACTSapodilla (Manilkara zapota (L.) van Royen) is a perishable fruit that exhibits rapid deterioration after harvesting. Low temperature storage has been extensively used to extend the storage life of many fresh commodities, however it is still rarely used for sapodilla. UV-C radiation has been studied for its capability to inhibit fruit ripening and senescence, and hence prolonging the period of fruit salability. This UV-C radiation might be a pre treatment for sapodilla before storage at low temperature. The objective of this research was to extend the storage life of sapodilla fruits by retarding ripening process through UV-C radiation and low temperature storage. Sapodilla fruits were exposed to four levels of UV-C exposure time i.e. 0 (no radiation), 5, 10, and 15 minutes, then stored at room temperature (27,13–28,11oC) and low temperature (16,70–18,13oC). Observations were taken on fruit respiration and ripening, and other related variables. The results showed that there was no interaction between UV-C radiation and storage temperature. The UV-C radiation did not significantly inhibit fruit ripening, thus did not inhibit the fruit senescence and deterioration. Keeping the fruit at low temperature inhibit fruit ripening and prolong its shelf life 6 days longer than those stored at room temperature. Key words : Sapodilla, UV-C radiation, low temperature storage, ripening, deterioration.